The assessment of antimalarial drug efficacy in vivo - White, NJ (Cell Press, 2022)
Currently recommended methods of assessing the efficacy of uncomplicated falciparum malaria treatment work less well in high-transmission than in low-transmission settings. There is also uncertainty how to assess intermittent preventive therapies and seasonal malaria chemoprevention (SMC), and Plasmodium vivax radical cure. A pharmacometric antimalarial resistance monitoring (PARM) approach is proposed specifically for evaluating slowly eliminated antimalarial drugs in areas of high transmission. In PARM antimalarial drug concentrations at recurrent parasitaemia are measured to identify outliers (i.e., recurrent parasitaemias in the presence of normally suppressive drug concentrations) and to evaluate changes over time. PARM requires characterization of pharmacometric profiles but should be simpler and more sensitive than current molecular genotyping-based methodologies. PARM does not require parasite genotyping and can be applied to the assessment of both prevention and treatment.